Teachers' Perceptions on the Use of Fairy Tales through Visual Media in Teaching English at SDN 006 Kubang Jaya - Kurnia Budiyanti; Olfita Rosma Sarah; Dinda Salsa Bella; Andika Madani Putra Sirait; Muhammad Dzakwan (Institut Teknologi Pendidikan Indonesia, 2026)
This study investigates English teachers' perceptions of the use of fairy tales through visual media in teaching English at the elementary school level. Conducted at SDN 006 Terpadu Kubang Jaya, this descriptive qualitative research involved two English teachers as participants. Data were collected through a Likert scale questionnaire and semi-structured interviews. The findings reveal that both teachers hold highly positive perceptions regarding the integration of animated fairy tale videos in English instruction. Visual media, particularly animated stories accessed via YouTube and projected through LCD projectors, were found to significantly enhance students' vocabulary acquisition, motivation, classroom participation, and overall engagement. The teachers also reported that fairy tales effectively convey moral values alongside linguistic content, making them doubly beneficial for young learners. Despite minor infrastructural challenges such as limited projectors and unstable internet connections, the overall pedagogical impact was considered substantial. The study concludes that fairy tale-based visual media constitute an effective, motivating, and contextually appropriate tool for EFL instruction in Indonesian elementary classrooms, and it calls for greater institutional support to sustain and expand technology-integrated teaching practices.